Combination of Cysteine and Glutathione Prevents Ethanol-Induced Hangover and Liver Damage by Modulation of Nrf2 Signaling in HepG2 Cells and Mice - Hyeongyeong Kim; Hyung Joo Suh; Ki-Bae Hong; Eun-Jin Jung; Yejin Ahn (MDPI AG, 2023)
Excessive alcohol consumption increases oxidative stress, leading to alcoholic liver disease. In this study, the protective effects of a mixture of cysteine and glutathione against ethanol-induced hangover and liver damage were evaluated in mice and HepG2 cells. Ethanol (2 mL/kg) was orally administered to the mice 30 min before receiving the test compounds (200 mg/kg), and the behavioral and oxidative stress-related biochemical parameters altered by ethanol were analyzed. Acute ethanol administration increased anxiety behavior and decreased balance coordination in mice (p < 0.001); however, a mixture of cysteine and glutathione (MIX) in a 3:1 ratio improved alcohol-induced behavior more effectively than the individual compounds (p < 0.001). The MIX group showed higher ethanol-metabolizing enzyme activity than the control group (p < 0.001) and significantly suppressed the elevation of serum alcohol (p < 0.01) and acetaldehyde (p < 0.001) levels after 1 h of ethanol administration. In HepG2 cells, 2.5 mM MIX accelerated ethanol metabolism and reduced cytochrome P450 2E1 mRNA expression (p < 0.001). MIX also increased the expression of antioxidant enzymes through the upregulation of nuclear erythroid 2-related factor 2 (Nrf2) signaling and consequently suppressed the overproduction of reactive oxygen species and malondialdehyde (p < 0.001). Collectively, MIX alleviates the hangover symptoms and attenuates the alcohol-induced oxidative stress by regulating the Nrf2 pathway.